2020
DOI: 10.1080/07391102.2020.1814870
|View full text |Cite
|
Sign up to set email alerts
|

Identification of promising antiviral drug candidates against non-structural protein 15 (NSP15) from SARS-CoV-2: anin silicoassisted drug-repurposing study

Abstract: The recent COVID-19 pandemic caused by SARS-CoV-2 has recorded a high number of infected people across the globe. The virulent nature of the virus makes it necessary for us to identify promising therapeutic agents in a time-sensitive manner. The current study utilises an in silico based drug repurposing approach to identify potential anti-viral drug candidates targeting non-structural protein 15 (NSP15), i.e. a uridylate specific endoribonuclease of SARS-CoV-2 which plays an indispensable role in RNA processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Currently, there are no treatment measures or vaccination against SARS-CoV2, and the requirement of a prophylactic and therapeutic intervention technique is critical ( Shannon et al, 2020 , Sinha et al, 2020 , Walls et al, 2020 ). Targeting the conserved Nsp15 active site via potent inhibitor molecules will not only hinder its involvement in virus replication activity but also prohibit the protein from interfering with the host’s innate immune response, enabling it to fight the viral invasion ( Chandra et al, 2020 , Khan et al, 2020 , Surti et al, 2020 ). The current investigation was performed with the aim of finding potent inhibitor molecules that could strongly bind to the active site of Nsp15.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no treatment measures or vaccination against SARS-CoV2, and the requirement of a prophylactic and therapeutic intervention technique is critical ( Shannon et al, 2020 , Sinha et al, 2020 , Walls et al, 2020 ). Targeting the conserved Nsp15 active site via potent inhibitor molecules will not only hinder its involvement in virus replication activity but also prohibit the protein from interfering with the host’s innate immune response, enabling it to fight the viral invasion ( Chandra et al, 2020 , Khan et al, 2020 , Surti et al, 2020 ). The current investigation was performed with the aim of finding potent inhibitor molecules that could strongly bind to the active site of Nsp15.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to velpatasvir, paritaprevir is an antiviral agent against the HCV protease complex that gained a considerable amount of attention in the studies of COVID-19. Through tools like artificial intelligence (AI) deep learning, molecular docking, and, in some studies, molecular dynamics simulation, these investigations unanimously suggested the potential of paritaprevir in inhibiting viral RdRp, S protein, and proteases ( Manikyam and Joshi, 2020 , Shah et al, 2020 , Alamri et al, 2020 , Khan et al, 2020 , Choi et al, 2020 ). Our results expand the current paradigm and suggest that paritaprevir may also be used to target the NBD of csBiP, thereby sabotaging viral activities.…”
Section: Resultsmentioning
confidence: 99%
“…The MD simulation observations were quite similar to the current study in regards to stability, convergence and energetics. Khan et al [ 50 ] was performed an in-silico drug repurposing approach to find promising therapeutics targeting the Nsp15. From starting with more than a hundred known drugs, the authors reported three promising drug molecules effective against Nsp15.…”
Section: Resultsmentioning
confidence: 99%